Особенности расчета заземляющих устройств электроэнергообъектов - Колиушко, Денис Георгиевич (НТУ "ХПИ", 2008)
У статті наведенo розроблені способи для прискорення розрахунку заземлювальних пристроїв електроенергооб’єктів з великою кількістю вузлів сітки.

In article the developed methods for acceleration of calculation of the power industry objects grounding systems with a considerable quantity of the grounding grid nodes are resulted.
Keywords: ЗУ; системы линейных алгебраических уравнений; СЛАУ; комплексные значения напряжений; сжатый массив коэффициентов; аварийный режим